Implementasi Smart Govenrment melalui Program Sumbergedang Baru di Desa Sumbergedang Kecamatan Pandaan Kabupaten Pasuruan - Khalid Bahar Yusuf; Deby Febriyan Eprilianto; Muhammad Farid Maruf; M. Noer Falaq Al Amin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to describe the implementation of smart government through the Sumbergedang Baru Program in Sumbergedang Village, Pandaan District, Pasuruan Regency. The program is a digital village initiative that utilizes information technology to improve the quality of public services, transparency of governance, and the social and economic empowerment of rural communities. This study employed a descriptive qualitative approach with purposively selected informants, including the village head, village officials, community groups (Pokmas GPS and G4S), and residents as service recipients. The findings show that digital literacy among the community and village officials has begun to develop, as indicated by their ability to use basic devices and applications; however, the utilization of village digital services remains limited and uneven across age groups. In terms of ICT accessibility, the village has established an internet network and public Wi-Fi hotspots, yet network coverage and stability have not fully reached all hamlets. Regarding regulations, the village government has established basic policies through decrees forming community groups and regulating the digital village program, although these have not been comprehensively integrated. In terms of human resource quality, village officials and young cadres are relatively adaptive to technology, but a capacity gap remains among older age groups. Overall, the implementation of smart government through the Sumbergedang Baru Program is still at the stage of building a digital village foundation, requiring further improvements in digital literacy, human resources, infrastructure expansion, and technology-based transparency.